The Rise of The Rising Sun: The Roots of Japanese Imperialism in Mutsuhito Era (1868-1912) - Gema Budiarto (IZUMI, 2021)
This article aims to discuss the Japanese modernisation of the Mutsuhito Emperor Era, which focused on the developments that triggered Japan to become an imperialist country. The Bakufu government, which had been in power for more than 250 years, must finally end. After being deemed unable to handle the country's condition, the Bakufu government returned the Japanese government ultimately to Emperor Mutsuhito. During the occupation of the Empire's seat, Emperor Mutsuhito was assisted by his advisers to make changes in all fields. The main fields were built by them, such as reorganise the political bureaucracy, developing industrial-economic, and developing military technology. Supported by the progressive developments in the country, Japan was transforming into a large industrial nation. To meet its industrial needs, Japan became an imperialist country and defeated China and Russia during the Mutsuhito period of government. The method used in this research is historical and has five steps, among others determining the topic, sources collection, sources criticism, interpretation, and writing. The results showed that the aggressive development and strengthening in political bureaucracy, industrial economics, and military technology in the Meiji era were the roots of the spirit of imperialism of new Japan. Political, economic, and military are the reasons to undertake imperialism besides cultural and religious reasons